Nematode RALF-Like 1 Targets Soybean Malectin-Like Receptor Kinase to Facilitate Parasitism - Zhang, Xin; Wang, Dongmei; Chen, Jia; Wu, Dousheng; Feng, Xianzhong; Yu, Feng (Frontiers in Plant Science, 2021)
Soybean [Glycine max (L.) Merr. ] is one of the most strategical oilseed crops that provides sustainable source of protein and oil worldwide. Cultivation of soybean is severely affected by root-knot nematode (RKN). However, the mechanism of RKN parasitism to soybeans is largely unknown. In this study, we identify GmLMM1, which encodes a homolog of FERONIA-like receptor kinase in soybean, as a susceptible gene toward nematode. Mutations of GmLMM1 exhibit enhanced resistance against the RKN Meloidogyne incognita. RNA-sequencing (RNA-seq) analysis reveals a similar differential expression pattern for genes regulated by GmLMM1 (Gmlmm1 vs. wild-type) and M. incognita (M. incognita vs. mock), supporting the role of GmLMM1 in M. incognita infection. Unlike FERONIA in Arabidopsis, GmLMM1 specifically binds to MiRALF1 and AtRALF23 that suppress plant immunity, but not MiRALF3 and AtRALF1. Moreover, we found that the single-nucleotide polymorphism (SNP) in GmLMM1 leads to the natural resistance against RKNs in soybeans. Collectively, these findings uncover GmLMM1 as a susceptible target of nematode RALF-like 1 and provide new genetic resource for nematode resistant breeding.